The Role of Influencers in Bali Tourism Public Relations Bali: SWOT Analysis - Awaloedin, Dipa Teruna; Pradini, Gagih; Liora, Devina Nisa; Andini, Davi Ayu (CV ODIS, 2024)
Bali's tourism industry is a crucial economic pillar for the island, celebrated for its stunning natural landscapes, rich cultural heritage, and warm hospitality. However, the rapid growth of tourism has resulted in adverse environmental impacts, placing immense pressure on Bali's resources, environment, and local traditions. Amidst the global evolution of economic development, tourism continues to burgeon, driven by technological advancements and evolving consumer behaviours. In this digital age, public relations (PR) plays an increasingly pivotal role in shaping and safeguarding a destination's image, further accentuated by the emergence of influencers reshaping tourism marketing dynamics. Utilising social media platforms for sharing travel experiences has revolutionised marketing strategies, with influencer collaborations amplifying destination exposure and appeal. This paper aims to comprehensively analyse the role of influencers in tourism PR through a SWOT approach, exploring their significance, strengths, weaknesses, opportunities, and threats. By addressing critical questions and research objectives, this study aims to provide strategic insights into leveraging influencers effectively in Bali's tourism PR.